Effects of rapid process on the conductivity of multiple elements doped ceria-based electrolyte - Chang, Horng-Yi; Wang, Yao-Ming; Lin, Chia-Hsin; Cheng, Syh-Yuh (Journal of power sources, 2011)
[Display omitted] ▶ Microwave sintering reduces the grain boundary resistance of both SS and SV samples. ▶ The Schottky barrier height can be adjusted by SV powder preparation and by the MW process using a slightly lower sintering temperature and with a shorter processing time for multiple elements doped solid electrolyte. The citric acid-based combustion technique (SV) for powder preparation and the rapid microwave sintering (MW) process are used to lower the synthesizing temperature and to shorten the processing time then to modify the grain boundary resistance and oxygen vacancies mobility in multiple elements doped ceria-based electrolyte (LSBC). Nanoparticles of less than 50 nm with a pure fluorite structure are prepared by SV method at a low temperature of 600 °C. Microwave sintering lowers the sintering temperature to 1400 °C from the conventional sintering (CS) temperature of 1500 °C needed for solid-state (SS) prepared LSBC, and requires only 15 min of sintering time. The SV sample conventionally sintered at 1400 °C–6 h reaches a conductivity of 0.006 S cm −1. When the SV samples are microwave sintered at 1400 °C–15 min, they achieve a conductivity as high as 0.01 S cm −1 measured at 600 °C. Microwave sintering reduces the grain boundary resistance of both SS and SV samples. The migration enthalpy ( H m) of 0.66 eV in the SS-MW and SV-MW samples is similar to that of the fully densified SS-CS sample. The Schottky barrier height can be adjusted by SV powder preparation and by the MW process using a slightly lower sintering temperature and with a shorter processing time for multiple elements doped solid electrolyte.